PEMERIKSAAN MANAJEMEN TERHADAP FUNGSI PERSONALIA PADA PT. KRESNA REKSA FINANCE CABANG KENDARI - Abdullah, Muntu; Sarira, Caesarani Dolarosa (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACT             This research aims to determine the personnel function activity has been work effective as work planning, recruitment, selection and assessment specified management inspection on PT. Kresna Reksa Finance Branch Kendari.This research constitute qualitative descriptive research. Data were collected from observation, interview and documentation. Analysis method by using is qualitative analysis in a way describe Assessment of personnel function was done by some stages Management Inspection.            According to the research result it is known that the personnel function activity has been work effective as work planning, recruitment and assessment. While activity has not been work is a processes selection. Based on the findings contained in the weakness of the personnel function activity.Then given advice that can be used as input for management           to improve and enchance the effectiveness of the personnel function  namely, Improve management control on overall personell function that can be implemented effective, perform inspection corresponding general in order inspection program to create good control. Keywords       : Management Inspection, Personnel Function, Effective